2006
DOI: 10.1007/s10554-006-9145-0
|View full text |Cite
|
Sign up to set email alerts
|

Tei index in adult patients submitted to adriamycin chemotherapy: failure to predict early systolic dysfunction

Abstract: Tei index does not appear to be a useful tool for detection of early adriamycin cardiotoxicity in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…146,147 The prognostic value of myocardial performance index could not be replicated in subsequent studies. 148 Two studies have reported LV diastolic abnormalities late after anthracycline administration; these abnormalities were associated with wall motion abnormalities despite a preserved LVEF. 149 Another study reported that a reduced transmitral E/A ratio was associated with a reduction in longitudinal strain by STE in patients with normal LVEFs late after treatment.…”
Section: Diastolic Dysfunction: Early Signs and Prognostic Valuementioning
confidence: 99%
“…146,147 The prognostic value of myocardial performance index could not be replicated in subsequent studies. 148 Two studies have reported LV diastolic abnormalities late after anthracycline administration; these abnormalities were associated with wall motion abnormalities despite a preserved LVEF. 149 Another study reported that a reduced transmitral E/A ratio was associated with a reduction in longitudinal strain by STE in patients with normal LVEFs late after treatment.…”
Section: Diastolic Dysfunction: Early Signs and Prognostic Valuementioning
confidence: 99%
“…Our search yielded 212 potentially relevant studies. After a detailed review of titles, abstracts, and subsequently full articles for potentially relevant studies, 13 studies (1,14,15,16,17,18,19,20,21,22,23,24,30) were identified and included in the final review (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…According to the findings summarized in tables, it can be judged that myocardial damage in these patients are subclinical which is shown in MPI, and because of its progressive nature later engaged to involvement of EF and FS parameters. This process is justified through compensatory mechanisms that occur in the heart muscle (10, 19). In our study, tissue doppler showed a decreasing of IVRT in right and left ventricles in both groups, which is indicating improvement of left and right ventricular diastolic function after treatment.…”
Section: Discussionmentioning
confidence: 99%